2006
DOI: 10.1158/1055-9965.epi-05-0871
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Case-Control Study of VEGF Gene Polymorphisms and Breast Cancer Risk among Chinese Women

Abstract: Vascular endothelial growth factor (VEGF) is a major angiogenic factor involved in a number of pathologic processes, including neovascularization, a crucial step in the development of solid malignancies. Using data and specimens collected in the Shanghai Breast Cancer Study, a population-based case-control study conducted in urban Shanghai, China from 1996 to 1998, we evaluated the association of VEGF gene polymorphisms with breast cancer risk. Included in this study were 1,093 cases and 1,184 agematched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
8
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 30 publications
11
97
8
2
Order By: Relevance
“…Taking breast cancer as an example, similar frequencies of VEGF +936C/T genotypes between cases and controls were reported by Jacobs et al (2006). In contrast, Krippl et al (2003), Kataoka et al (2006), andJakubowska et al (2008) suggested that VEGF +936T is a protective factor against breast cancer. However, Balasubramanian et al (2007) found that VEGF +936C was associated with decreased breast cancer risk when combined with -460T and +405C.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Taking breast cancer as an example, similar frequencies of VEGF +936C/T genotypes between cases and controls were reported by Jacobs et al (2006). In contrast, Krippl et al (2003), Kataoka et al (2006), andJakubowska et al (2008) suggested that VEGF +936T is a protective factor against breast cancer. However, Balasubramanian et al (2007) found that VEGF +936C was associated with decreased breast cancer risk when combined with -460T and +405C.…”
Section: Introductionsupporting
confidence: 56%
“…The exact mechanism for how VEGF +936C/T acted on the carcinogenic procedure was not clear. In recent years, intense genetic research efforts have been made in this field, and the results produced have been conflicting (Krippl et al, 2003;Jacobs et al, 2006;Kataoka et al, 2006;Balasubramanian et al, 2007;Jakubowska et al, 2008). The leading potential explanation for the association was that the DNA sequence variation may alter VEGF production and/or activity (Renner et al, 2000), thereby causing differences in the development of tumors (Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results found that the 936CT+TT genotypes of VEGF reduced BRCA1-associated breast cancer risk in Polish women (Jakubowska et al, 2008). A population-based case-control study conducted in urban Shanghai, China from 1996 to 1998, suggested that the VEGF C936T polymorphism might be a susceptibility factor for breast cancer among Chinese women (Kataoka et al, 2006). A large case-control study found that the VEGF -634CC genotype and the VEGF -2578/-634 CC haplotype were significantly associated with high tumor aggressiveness (large tumor size and high histologic grade) and the VEGF -2578AA genotype and the VEGF -2578/-634 AG haplotype with low histologic grade tumors (Jin et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…The associations between three VEGF gene polymorphisms (-634 G/C, +936 C/T, and +1612 G/A) and breast cancer risk have been extensively studied, and the currently available results are inconclusive (Krippl et al, 2003;Jin et al, 2005;Lu et al, 2005;Jacobs et al, 2006;Kataoka et al, 2006;Eroglu et al, 2008;Jakubowska et al, 2008;Langsenlehner et al, 2008;Schneider et al, 2008;Wehrschuetz et al, 2009;Gu and Wang, 2011;Jin et al, 2011;Liu et al, 2011;Oliveira et al, 2011;Qiu et al, 2011;Wang et al, 2011;Yang et al, 2011;Rodrigues et al, 2012). The aim of this study was to investigate the association between three VEGF gene polymorphisms and breast cancer risk in Chinese Han patients.…”
Section: Introductionmentioning
confidence: 96%